Movimentos sociais urbanos: a produção do espaço e a luta pela moradia na cidade do Crato - Ceará - Oliveira Filho, João César Abreu de (2014)
This paper aims to discuss the social movements struggling for housing in Crato and the process of production of urban space from the fight and action of these movements. Initially we did a historical survey of the major struggles and movements that occurred in the city, especially in the 1970s and 1980s , when there was a ferment of forms of action of social movements in Crato . The church in this period had an important role in the construction and organization of social movements struggling for housing in the city, from the theory of liberation theology , and the progressive wing of the Catholic Church in Crato incisively influenced massively and the struggle for bit in the city , later the leftist political parties , like the PT and PC do B came into play in the organization of social struggles . Still , we did a theoretical approach arguing that residents' associations are a social movement or even a step of building a social movement , but there is dialectically to that, associations are also an appendix of political logic of the state or even groups local politicians interfered , thus the construction of a unified struggle for housing. Thus , it is understood that social movements struggling for housing in Crato , are organized or even factual and circumstantial a form of organization of the working class struggle for better living conditions and survival or in search of the right way to town .